Interaksi Edukasi Pengasuh dalam Memotivasi Santri Menghafal Al-Qur’an di Pondok Pesantren - Muhammad Yunus; Ismail Ismail; Agussalim Agussalim (TADRIBUNA: Journal of Islamic Education Management, 2025)
This study aims to analyze the role of educational interactions between caregivers in motivating students to memorize the Qur'an at the Darul Ihsan Islamic Boarding School in South Konawe. The research method used a qualitative case study approach with in-depth interviews, observations, and documentation of 10 caregivers and 15 students. Data analysis was conducted thematically. The results showed that educational interactions contributed significantly to students' memorization motivation through intensive guidance, motivational reinforcement, spiritual role models, and memorization techniques that suited the individual's cognitive character. Students' motivation was influenced by internal factors such as intention and commitment as well as external factors such as family support and the Islamic boarding school environment. Caregivers addressed memorization challenges through a variety of methods, emotional support, and educational-recreational activities.